ANALISIS FAKTOR HARGA BERAS DI INDONESIA TAHUN 1979 - , RUFAIDA ANNY S. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Food is one of the three basic human needs. Food needs in Indonesia has a broad meaning and complex in which the availability, distribution and affordability by purchasing power becomes a major issue in national economic policy. Food products that became the mainstay of the people of Indonesia is rice. Where 98 percent of the Indonesia people is have rice as a staple food (Riyadi in Kusumaningrum (2008)). Because rice is the staple food, the increased consumption of rice and rice price movements can affect the stability of the existing food system. This study aims to determine the factors that affect the change of rice price in Indonesia. The estimation method used was Ordinary Least Square (OLS) and the Autoregressive Distributed Lag (ADL) with a span of years from 1979 to 2011. Factors thought to affect the rice price such as rice production, the wheat price, the number of rice imports, and population. The results showed the shortterm that wheat price and rice imports has a positive effect on rice price. While in the long-term, rice import has positive impact on rice price. The rice price of the earlier year has positive influence on rice price this year.